Galician Matriarchy, Basque Matriarchy: Myth Revision in Álvaro Gago’s "Matria" and Asier Altuna’s "Amama" - Boguszewicz, Maria; Gajewska, Magdalena Anna (Madrygal. Revista de Estudios Gallegos, 2020)
The article analyzes the representations of the female figure in two films that poses the issue of matriarchy in, respectively, the Galician and Basque culture: the short film Matria by Álvaro Gago (2017) and the feature film Amama by Asier Altuna (2015). Our goal is to reflect on how these films construct the image of women, what types of “feminities” they reproduce, from what perspective raise questions about female power and through which strategies review the concept of matriarchy. The study is based on the “anthropological-morphological method of film analysis” by Seweryn Kuśmierczyk founded on the idea that film reality, being a sublimated image of the world outside the screen, reflects the sociocultural context in which the film arises. In the conclusions we refer to the ambiguity of the interpretations of the feminine condition represented in the analyzed films. In spite of different attitudes of their authors towards the concept of matriarchy and in spite of using totally different languages, in the case of both films emerges their potential to deconstruct the myth of Galician and Basque matriarchy and to formulate a critical commentary about reality.